2008
DOI: 10.1007/bf03395616
|View full text |Cite
|
Sign up to set email alerts
|

How Sex, Native Language, and College Major Relate to the Cognitive Strategies Used during 3-D Mental Rotation

Abstract: Eighty college students mentally rotated 3-D shapes while maintaining a con

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…In this style, the user can mentally rotate the object with holistic processing and analytical processing based on some features of the object. The later studies by Li [12], [13], [14], [10], [15] noticed and concluded that the females are tending and preferring to use the combined strategy or analytical strategy.…”
Section: Combined Mental Rotationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this style, the user can mentally rotate the object with holistic processing and analytical processing based on some features of the object. The later studies by Li [12], [13], [14], [10], [15] noticed and concluded that the females are tending and preferring to use the combined strategy or analytical strategy.…”
Section: Combined Mental Rotationmentioning
confidence: 99%
“…Many researches by Li [12], [13], [14], [10], [15] concluded that males outperform females in a most of spatial tasks, particularly when they involve mental rotation tests. "Males tend to outperform women on spatial reasoning tests significantly.…”
Section: Gender Differencesmentioning
confidence: 99%
“…A similar pattern emerges when comparing students of different college majors performing the Piagetian water-level task, which is considered a reliable index of spatial ability (Kalichman, 1986). Importantly, a small number of studies suggest that individuals majoring in the physical sciences rely on a different mental strategy to perform MR as compared to social science majors; though not unanimously so, the majority of college students majoring in the physical sciences utilize a spatial/holistic strategy, whereas those majoring in the social sciences employ either a verbal/analytic or combined (i.e., verbal/analytic and spatial/holistic) MR strategy (Casey, Winner, & Benbow, 1993;Lavach, 1991;Y. Li & O'Boyle, 2008;Zegas, 1976).…”
Section: Neural and Linguistic Differences Between Native English Andmentioning
confidence: 99%
“…For instance, when the Tenejapan Mayan people (native speakers of Tseltal who primarily use a geocentric spatial coordinate system) and native Dutch speakers (who primarily use an egocentric representational system) were shown pictures of objects and then asked to select the identical picture from a set of four pictures rotated 180 degrees relative to their body, each group chose different pictures: Specifically, they chose the one that best mapped on to the spatial representational system emphasized by their respective languages (Majid, Bowerman, Kita, Huan, & Levinson, 2004). Interestingly, P. Li, Abarbanell, and Papafragou (2005) found that native speakers of Tseltal can conceptually reason about left/right positioning despite the fact that their native language does not contain corresponding words for this relational system. Note that the latter capability argues against an overly strong linguistic relativity position.…”
mentioning
confidence: 99%
“…At the level of higher order cognitive functioning, Agor (1984Agor ( , 1989 found that some people tended to use an analytical approach, breaking a problem down into manageable parts, whereas others tended to use an intuitive approach. Individual differences have also been 42 XU found through research on learning styles in educational settings (e.g., Entwistle, Hanley, & Hounsell, 1979;Gregorc, 1982;Li & O'Boyle, 2008). In a recent review of the literature, Kozhevnikov (2007) introduced Nosal's model about individual differences at different levels of information processing.…”
mentioning
confidence: 97%